FORAMINIFERI PLIO-PLEISTOCENICI DEL VERSANTE SETTENTRIONALE DEI MONTI PELORITANI: ANALISI BIOSTRATIGRAFICA E PALEOAMBIENTALE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
This study deals with the foraminiferal assemblages of Plio-Pleistocene sediments of the northern side of the Peloritani Mountains (North-Eastern Sicily). Six sections were closely sampled in the surroundings of Rometta (Sottocastello Sud, Sottocastello, Torrione, Sperone, Sottorometta, Rometta}, three in nearbyvalleys (Torretta, S. Sehastiano, Serro), and three others come from a quarry in the northern plain toward the Tyrrhenian Sea (Villafranca Tirrena).
Keywords: Foraminifera; Biostratigraphy; Paleobathymetry; Pliocene; Early Pleistocene; North-Eastern Sicily.